2009
DOI: 10.1136/thx.2008.104703
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in pregnancy and respiratory and atopic outcomes in childhood

Abstract: Background: Studies of the relation between maternal diet in pregnancy and respiratory and atopic outcomes in the offspring have focused on the effects of individual nutrients and foods rather than dietary patterns. A study was undertaken to determine whether dietary patterns in pregnancy are related to childhood asthma and related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 49 publications
5
114
0
3
Order By: Relevance
“…Shaheen et al [62] found no significant associations between mothers' dietary patterns while pregnant and development of asthma in their children at 7.5 years of age. The retrospective study of De Batlle et al [57] also failed to show differences for wheeze in the children.…”
Section: At 6 To 8 Years Of Agementioning
confidence: 99%
See 3 more Smart Citations
“…Shaheen et al [62] found no significant associations between mothers' dietary patterns while pregnant and development of asthma in their children at 7.5 years of age. The retrospective study of De Batlle et al [57] also failed to show differences for wheeze in the children.…”
Section: At 6 To 8 Years Of Agementioning
confidence: 99%
“…Shaheen 2009 [62] found no significant associations between childhood eczema at seven years of age and maternal dietary patterns during pregnancy.…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…First is the possibility that taking acetaminophen increases airway inflammation in people with asthma or a predisposition to asthma contributing to the severity and frequency of symptoms. Second is the possibility that those exposed to acetaminophen in utero 3,21,22 or in the first year of life might be more likely to develop asthma later in childhood. My decision to discourage acetaminophen use in children with asthma is based on data that support the first of these 2 possibilities.…”
mentioning
confidence: 99%